YouTube as a Learning Tool: Shaping English Proficiency and Daily Phrases in a Young Dayakese - Novely Esterika Paulina; Elanneri Karani; Indra Perdana; Joni Bungai (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study explores a young Dayakese individual's acquisition of English spoken expressions through YouTube as a learning medium. Employing a qualitative case study design, data were collected from naturalistic observation, semi-structured interviews with the subject’s mother and aunt, and documentation of daily English utterances from video recordings spanning the subject’s development from infancy to age seven. The population consists of children in a multilingual Dayakese-speaking environment, with a purposive sample focusing on one child with frequent exposure to English content on YouTube. Data were analyzed through transcription, categorization, and thematic analysis to examine pronunciation, vocabulary acquisition, fluency, and grammatical development. The findings highlight YouTube's potential as an accessible and effective language learning tool in communities where English is not the dominant language, offering valuable insights for educators, parents, and language learners.